Sociology and Reflexivity - Valantiejus, Algimantas (Problemos, 2002)
The aim of the article is to explore the concept of methodological reflexivity by specifying the historical aspects of its contemporary development and by casting light on the pluralistic and fragmentary character of contemporary sociological thought. The contemprary sociological identity has been shaped in reference to some negative discrepancy between the postpositivistic and the modernist principles. As the self-sufficient social facts or the reality suí generis is treated with distrust, the emphasis is laid upon contextual, pragmatic aspects of academic activity. Unlike the conventional sociology which was not concerned of how the forms of sociological explanation were systemically incorporated and implemented in ordinary scientific practices, the sociological concept of reflexívity of last decades was formulated as the integral part of sociological inquiry, aimed at the methodological complexity and actual practice of social sciences. ln any case, the sum of latter-day sociological inquiry, as compared with the traditional attempt to apply one and the only theoretical synthesis, shows that under the new perspective the sociology undergoes a radical reframing. The new sociological identity is being shaped by l) fragmentary and relative context; 2) the attempts of reflexive methodology to systemically and critically evaluate the social-scientific accounts of reality; 3) the skeptical treatment of “representations"; 4) the “performative" character of critical activity; 5) experience of indeterminacy conditioned by a) the antithesis between the conventional and the new theoretical projects; b) the social aspects of scientific activity which include the conversational, discursive and reflexive dimensions.